Prevalence of Preeclampsia,Risk Factor and Pregnancy outcomes: A Comprehensive Systematic Review - Siman, Pratiwi; Yulindar, Vivin (The International Journal of Medical Science and Health Research, 2024)
Background: Preeclampsia, a maternal health condition, has a significant impact on 10% of pregnancies. Risk factors gestational hypertension, and chronic hypertension increase the risk of preeclampsia, leading to stroke, cardiovascular death, and long-term hypertension for both mother and fetus. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. The literature was assembled using a variety of online databases, including ScienceDirect, PubMed, and SagePub. Result: Following a rigorous three-stage screening procedure, six papers were found to have relevant links to our current extensive inquiry. Conclusion: Pregnancy is a critical time, and preeclampsia, associated with high prevalence, significantly impacts pregnancy outcomes. Factors like obstetric history, maternal illnesses, and hypertension disease can lead to unfavorable outcomes. Preventative measures, lifestyle changes, and optimalization of vitamin D can reduce risk of preeclampsia.